MicroRNA-455-3p improves synaptic, cognitive functions and extends lifespan: Relevance to Alzheimer's disease - Subodh Kumar (Elsevier, 2021)
Background: MicroRNA-455-3p is one of the highly conserved miRNAs involved in multiple cellular functions in humans and we explored its relevance to learning and memory functions in Alzheimer's disease (AD). Our recent in vitro studies exhibited the protective role of miR-455-3p against AD toxicities in reducing full-length APP and amyloid-β (Aβ) levels, and also in reducing defective mitochondrial biogenesis, impaired mitochondrial dynamics and synaptic deficiencies. In the current study, we sought to determine the function of miR-455-3p in mouse models. Methods: For the first time we generated both transgenic (TG) and knockout (KO) mouse models of miR-455-3p. We determined the lifespan extension, cognitive function, mitochondrial biogenesis, mitochondrial dynamics, mitochondrial morphology, dendritic spine density, synapse numbers and synaptic activity in miR-455-3p TG and KO mice. Results: MiR-455-3p TG mice lived 5 months longer than wild-type (WT) counterparts, whereas KO mice lived 4 months shorter than WT mice. Morris water maze test showed improved cognitive behavior, spatial learning and memory in miR-455-3p TG mice relative to age-matched WT mice and miR-455-3p KO mice. Further, mitochondrial biogenesis, dynamics and synaptic activities were enhanced in miR-455-3p TG mice, while these were reduced in KO mice. Overall, overexpressed miR-455-3p in mice displayed protective effects, whereas depleted miR-455-3p in mice exhibited deleterious effects in relation to lifespan, cognitive behavior, and mitochondrial and synaptic activities. Conclusion: Both mouse models could be ideal research tools to understand the molecular basis of aging and its relevance to AD and other age-related diseases.